Gut Microbiota in T2DM Patients with Microvascular Complications: A 16S rRNA Sequencing Study - Wang Y; Jiang D; Pan X; Sun K; Li T; Cao X; Zhu X (Diabetes, Metabolic Syndrome and Obesity)
Yuying Wang, Dongmei Jiang, Xia Pan, Ke Sun, Tingting Li, Xin Cao, Xiaohui Zhu Department of Endocrinology, Affiliated Hospital 6 of Nantong University, Yancheng Third People’s Hospital, Yancheng City, Jiangsu Province, People’s Republic of ChinaCorrespondence: Xiaohui Zhu, Department of Endocrinology, Affiliated Hospital 6 of Nantong University, Yancheng Third People’s Hospital, Yandu District, Yancheng City, Jiangsu Province, 224000, People’s Republic of China, Tel +86 18344764511, Email zhuxiao_hui9@163.comObjective: This study aims to investigate the characteristics of gut microbiota in patients with microvascular complications of Type 2 Diabetes Mellitus (T2DM) using 16S rRNA high-throughput sequencing technology.Methods: Patients diagnosed with T2DM were enrolled as study subjects. Based on the presence of microvascular complications, subjects were divided into a study group, a control group. Clinical fecal samples from the two groups were subjected to diversity analysis using the Illumina MiSeq high-throughput sequencing technology, comparing the richness and diversity of the gut microbiota between the two groups. The Tax4Fun software was utilized for the functional prediction of differential microbiota.Results: A total of 3727 operational taxonomic units (OTUs) were identified, with 1311 OTUs common to both groups, and 1363 and 1053 OTUs unique to the study group and the control group, respectively. The study group exhibited a significant increase in the relative abundance of Clostridia and Negativicutes, and a marked decrease in Gammaproteobacteria, Bacilli, and Verrucomicrobia compared to the control group. LefSe analysis revealed significant differences in the relative abundance at two phyla, two classes, two orders, three families, and two genera levels between the groups. KEGG pathway analysis of differential microbiota identified 10 pathways with statistically significant differences (P< 0.05).Conclusion: This study reveals significant disparities in gut microbiota abundance between T2DM patients and those with microvascular complications of T2DM, suggesting potential microbial markers for diagnosing and treating microvascular complications of T2DM.Keywords: 16S rRNA sequencing, type 2 diabetes, microvascular complications, gut microbiota